Wetting characteristics of artificial contamination on the hydrophobic surface. (June 2019) - Cao, Bin; Wang, Liming
Abstract: Pollution flashover has a significant influence on the stable operation of power system. Pollution accumulation and wetting of insulator are the two prerequisites for the pollution flashover. In this paper, the wetting characteristics of artificial contamination on the silicone rubber surface are studied. The results showed that the wetting process of hydrophobic surface differed greatly from the hydrophilic surface. After the silicone rubber contaminated, the sodium chloride originally mixed evenly in the contamination layer gradually recrystallized and precipitated out of the layer during the drying process. Due to the recrystallization phenomenon, water drops were produced firstly at the location of sodium chloride crystals regardless of hydrophobicity. The newly formed small water drops exhibited the highest salinity and then the salinity decreased gradually over time in the wetting process. The soluble salts on the area between the water drops on silicone rubber surface were also dissolved partially. The results might provide a reference for the artificial contamination test of composite insulators. Highlights: Wetting characteristics of artificial contamination on the hydrophobic surface are experimentally studied. Due to recrystallization, droplets were produced firstly at the location of NaCl crystals regardless of hydrophobicity. The newly formed water drops exhibited the highest salinity and the salinity decreased gradually in the wetting process. The contamination between droplets are partially dissolved and the dissolved amount is related to the hydrophobicity.